The Influence of Sustainable Captured Fish Supply Chain Management on the Quality of Sea-Caught Fish Exports - Ariffien, Afferdhy; Sudirman, Iman; Juniati, Atty Tri (Yayasan Ilomata, 2024)
A report from the Ministry of Maritime Affairs and Fisheries explains that Indonesia's total fishery exports in September 2023 will reach US 4.1 billion (Rp. 64.1 trillion). This figure is still far from the target to be achieved, namely US 7.8 billion in 2023. The aim of this research is to accelerate the development of the National Fisheries Industry which is at the forefront. Take the example of the fisheries supply chain in Cilacap Regency which is the largest producer of caught fish on the island of Java. By using the Soft System Research Methodology (SSM), the efforts made are to outline solutions to unstructured problems, understand the actual problem situation and take action to improve it. From the survey results, there are six problems in the supply chain of capture fisheries industry activities in Cilacap Regency, namely lack of facilities and infrastructure, lack of understanding and knowledge of fishermen, limited capital for capture fisheries businesses, excessive fishing, fishing community culture and weak supervision/law. Meanwhile, the research results show that in an ideal marine fisheries industry supply chain system, Cilacap Regency must carry out coordination and communication activities between caught fish supply chain actors, provide facilities and infrastructure, build logistics networks, standardize production, control storage methods, build systems monitoring, quality assurance of fisheries, and building a capture fisheries trading system. The implications include providing education to fishermen regarding marketing, collecting information about consumers and their needs, developing and developing fishermen's competence, government supervision, building local fishermen's cooperatives and maintaining traditional values.